If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x=4=-20
We move all terms to the left:
-6x-(4)=0
We move all terms containing x to the left, all other terms to the right
-6x=4
x=4/-6
x=-2/3
| 3-5=4x-7(1-5x) | | 15s=15(-3) | | -3t=-6/7 | | 2.75+0.10x=x | | 34(x-10)=12(x-12) | | 3x-14=7x+22 | | x²-7x+3=0 | | 171+9m=297 | | 2(n-3)=4n-2 | | 5y+1=3y-11 | | −5x+13x=64 | | 7x−4x=27 | | 2.99*f=45 | | 23n-95=342 | | -52x-22=-47+43-5x | | −10x−5x=45 | | 6x−5+7x=34 | | -24=-8+u/4 | | 11x-27=17 | | 189=-6x+2(-7x-18 | | (13+x)-12=20 | | 189=-6x+2(-7-18) | | 2.5x-12=0.5x+24.6 | | 5x-29=2x-2 | | 4(2x+4)=-4 | | -18=-3c | | 1/3m=36 | | 17=−6t−7 | | 5x-20=3(×+10) | | 4n+2=(1/3n-2/3) | | x=(25x5)+75-(20÷4)* | | 4(-2x+3)=-7x-8 |